Characterization and genotyping of the DRB1 gene of the major histocompatibility complex (MHC) in the Marmota monax, animal model of hepatitis B. Issue 2 (February 2015) - Moreno-Cugnon, Leire; Esparza-Baquer, Aitor; Larruskain, Amaia; García-Etxebarria, Koldo; Menne, Stephan; González-Aseguinolaza, Gloria; Jugo, Begoña M.
Highlights We have characterized the DRB1 exon 2 region in Marmota monax. The detected 15 alleles were classified in two clusters named DRB1-A and DRB1-B. Positive selection acting in both clusters was observed. Low heterozygosity was obtained due to the elevated rate of null alleles. A microsatellite that could allow the semiautomatic sequencing was identified.